Pengembangan Karakter Mulia melalui Pendekatan Story Telling di MI - Hafizah Luthfiah Adlin; Nadia Iksa; Gusmaneli (GLOBAL SCIENTS PUBLISHER, 2025)
The storytelling approach is a learning method increasingly used in elementary education, particularly in Islamic elementary schools (MI), to instill noble character values ​​in students. Through the delivery of engaging and relevant stories, storytelling can connect moral concepts with children's concrete experiences, thus making the internalization of values ​​more effective. This study discusses the meaning of storytelling in the context of character development, the challenges teachers face in implementing it, its positive impacts, and strategies that can be implemented to increase its effectiveness. Various findings indicate that storytelling not only strengthens students' understanding of religious, social, and national values ​​but also improves empathy, communication, and emotional interaction in learning. However, several challenges such as limited teacher competence, a lack of contextual teaching materials, and minimal family support hinder implementation. Therefore, the success of storytelling is highly dependent on teacher training, integration into lesson plans, the provision of engaging learning media, and synergy between schools and parents. This approach has the potential to be an effective strategy for strengthening children's character sustainably if implemented consistently and in a planned manner.